The Protective Factor of Diarrhea Incidence in Toddler in Surabaya - Rachmah Wahyu Ainsyah; Muhammad Farid Lusno (Universitas Airlangga, 2018)
Background: Basic health research in 2013 found that diarrhea incidence in toddler was the highest. The working area of a public health center in Wonokusumo Surabaya found that the diarrhea incidence in toddler increased from 62 cases in 2015 to 385 cases in 2016. Purpose: This study was aimed to analyze the protective factor of diarrhea. Methods: This study was analytic observational with a cross sectional design. The study was conducted from 18 January to 23 February 2013 in community group (RW) 2 in Wonokusumo region, Surabaya city. The population of this study consisted of 210 mothers who had toddlers. There were 67 respondents selected through simple random sampling. Data were collected through questionnaire and observation and analyzed with multiple logistic regression. Results: These variables had significant influence on diarrhea incidence simultaneously, namely protected water resource utilization (PR = 0,10; 95% CI = 0,02 < PR < 0,64), healthy latrine utilization (PR = 0,06; 95% CI = 0,01 < PR < 0,50), washing hand habit (PR = 0,10; 95% CI = 0,01 < PR < 0,72), and monthly body weight measurement participation (PR = 0,04; 95% CI = 0,01 < PR < 0,29). The other variables such as mother's employment, wage according to city minimum wage, and breastfeeding history. Conclusion: The protective factors of this study were the utilization of protective water resource, good latrine utilization, washing hand habit, and body weight measurement participation.